Induction of a biostimulant and response in the biochemical activity of Ocimum basilicum L. under salinity - Batista-Sánchez, Daulemys; Murillo Amador, Bernardo; Ojeda-Silvera, Carlos Michel; Mazón-Suástegui, José Manuel; Preciado-Rangel, Pablo; Ruiz-Espinoza, Francisco Higinio; Aguero-Fernández, Yuneisy Milagro (Ecosistemas y Recursos Agropecuarios, 2022)
The biostimulants contain substances that support secondary plant metabolism when are available. In addition to stimulate plant growth and development, they activate physiological functions in plants, because of they contain molecules associates to plant metabolism. The objective of this study was to evaluate the mitigating effect of one biostimulant on the proline content, total proteins, and enzymatic activity of three varieties of basil subjected to NaCl stress. The experimental design was completely randomized with factorial arrangement. Factor A were three varieties (Napoletano, Nufar and Emily), factor B were four concentrations of NaCl (0, 50, 100 and 150 mM) and factor C, two doses of the biostimulant (0 and 0.5 mL L-1) with four replications. The proline content, total proteins, superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) activity were determined in leaves and roots. The results showed that basil varieties increased the concentrations of proline, CAT, SOD and GPx as the NaCl concentrations ranged from moderate to severe (100 and 150 mM NaCl). The plants treated with 0.5 mL L-1 of the biostimulant, significantly increased the biochemical variables, even under NaCl-stress, determining the mitigating effect of the biostimulant by promoting a greater enzymatic activity and an increase in osmoregulatory substances.